Identificação de inibidores oriundos de fontes naturais para o modelo do receptor atpase-ca+2 do Plasmodium falciparum (PfATP6) - Santos, Elisângela (2014)
Malaria is considered a non-contagious chronic evolution with episodic manifestations of acute character infectious disease, which afflicts millions of people in tropical and subtropical areas of the world. Vegetables represent a source of active molecules for various diseases, including malaria. Through phytochemical procedures, one can study the secondary metabolism of these plants where they hope to find new sources of treatment for malaria. The present study had as main objective to identify molecules derived from natural sources can inhibit the ATPase-Ca 2 + protein of Plasmodium falciparum (PfATP6). The molecular target was the model PfATP6 receiver, obtained by comparative modeling. Was performed using the program AutoDock Vina 1.1.2. screening in databases with the aim of selecting the 10 most promising ligands, with determination of the energies of affinity. Subsequently, tests with hydromethanolic and chloroform extracts of the species of Tul Cenostigma macrophyllum were performed. The patterns of agatisflavona and amentoflavone biflavonoids were analyzed by High Performance Liquid Chromatography for Detection Arrangement Diodes (HPLC-DAD) to identify the presence of these metabolites in the species. Validation of the chromatographic method took into account the parameters selectivity, linearity, precision, accuracy, limit of detection and limit of quantification. The results showed molecular next coupling energy variation among the 10 selected compounds (1 kcal / mol). With the results of the molecular coupling of the intermolecular interactions were studied and agatisflavona amentoflavone with PfATP6 receiver comparing them with the values obtained for thapsigargin. Since the energy values affinity the compounds amentoflavone -10.0 kcal / mol and agatisflavona -9.7 kcal / mol ortostérico showed affinity for the receptor site of PfATP6, these interactions being supported by the nature of intermolecular interactions identified. By comparing the retention times and ultraviolet spectra (UV) of the standards and samples could be identified agatisflavona amentoflavone and biflavonoids the leaves and stem bark of C. macrophyllum. Quantification of agatisflavona biflavonoide ranged from 22.25 to 0.012 mg of agatisflavona / g dry plant and amentoflavone ranged from 20.63 to 0.02 mg of amentoflavone / g dry plant. The analysis of the parameters evaluated showed that the method was suitable for the analysis of agatisflavona and amentoflavone, performing in line with the specifications of the current legislation. It is noticed that the amentoflavone agatisflavona compounds and can act in PfATP6 receiver, directing further studies of interactions in biological target in perspective for malaria control. Thus, it is possible to suggest that there are natural compounds present in semiarid with possible antimalarial activity, wherein the molecular modeling tool associated with the phytochemical analysis can guide the identification of bioactive compounds, and therefore the development of new drugs.